Mexico's Community Forest Enterprises : Success on the Commons and the Seeds of a Good Anthropocene - Bray, David Barton (Book collections on Project MUSE., 2020)
"David Barton Bray has spent more than thirty years researching and studying Mexican Community Forestry Enterprises (CFEs). In this book he shares the scientific evidence for Mexico's social and environmental achievements and how, in its most successful manifestations, it became a global model for common property forest management, sustainable social-ecological systems, and climate change mitigation in developing countries"--